2012
DOI: 10.1007/s00268-012-1830-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Postoperative Recurrence and Hepatic and/or Pulmonary Resection for Liver and/or Lung Metastases From Esophageal Carcinoma

Abstract: Resection of pulmonary metastases yields a survival benefit in properly selected patients. The benefit of resection for hepatic metastases remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 34 publications
6
53
0
6
Order By: Relevance
“…However, two of the four patients remain disease free at 22 and 92 months, and in this group, particularly patient 2 who had unfavorable hepatic pathology, a survival advantage may have been offered by liver resection, although this cannot be proven from the present report. Our findings are comparable to the results of Ichida et al . who report five patients who underwent hepatectomy for esophageal liver metastases from their institution in Japan.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, two of the four patients remain disease free at 22 and 92 months, and in this group, particularly patient 2 who had unfavorable hepatic pathology, a survival advantage may have been offered by liver resection, although this cannot be proven from the present report. Our findings are comparable to the results of Ichida et al . who report five patients who underwent hepatectomy for esophageal liver metastases from their institution in Japan.…”
Section: Discussionsupporting
confidence: 91%
“…In their recent article, Ichida et al . postulate that although liver metastases are indicative of hematogenous metastases, hepatectomy may still offer curative treatment in those with a favorable tumor biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results: A univariate analysis showed that distant organ recurrence, the number of recurrent tumors, the longest diameter of the largest recurrent tumor, the sum of all of the longest diameters of the recurrent tumors, invasion into adjacent structures and the speed of growth of the representative recurrent tumors were significantly associated with the post-recurrence prognosis. A multivariate analysis showed that distant organ recurrence, the longest diameter of the largest recurrent tumor, invasion into adjacent structures and the speed of growth of the representative recurrent tumors were significantly associated prognosis [5][6][7] . Therefore, the circumstances regarding postoperative recurrence are changing, and aggressive multimodality treatments for recurrence have been developed to improve the post-recurrence prognosis [8] .…”
Section: Introductionmentioning
confidence: 99%
“…For recurrence of distant metastasis alone, a reasonable OS was also attained in the present study. If curative resection could be possible, surgery could be considered a curative option for distant metastasis, as recently proposed in esophageal cancer [26,27] . These findings suggest the novel notion that recurrences after NAC could be managed for cure by optimal multimodality treatments.…”
Section: Discussionmentioning
confidence: 99%